My sister's keeper [videorecording] - Johnson, Mark; Pacheco, Chuck (New Line Home Entertainment, 2009)
Sara and Brian live an idyllic life with their young son and daughter. Suddenly, their baby girl falls ill, and her only hope for survival rests in her parents' ability to find a compatible bone marrow donator. Their desperate decision to conceive another child raises both ethical and moral questions and begins to erode their relationship. Their actions ultimately set off a court case that threatens to tear the family apart.